Parents attending a family weight management program perceive similar home fruit and vegetable accessibility, but greater child proxy agency and physical activity opportunity - Rosenkranz, Richard R.; Geller, Karly S.; Dzewaltowski, David A. (My University, 2007)
Many children do not meet current guidelines for physical activity and fruit and vegetable consumption, two areas of health-related behavior with links to obesity. Objective: To examine child and parent perceptions of child proxy agency, home physical activity opportunity, and home accessibility of fruits and vegetables. Methods: Dyads (N = 117) of parents and children completed questionnaires for this cross-sectional study. Results: For child proxy agency, fruits and vegetables accessibility, and physical activity opportunity, the parent and child perceptions were significantly related. Parent ratings of physical activity opportunity and child proxy agency were significantly greater than child ratings. Perceptions of both parents and children for proxy agency were associated with fruits and vegetables accessibility and physical activity opportunity. Conclusions: Parents and children hold similar, yet distinct perceptions of physical activity opportunity and child proxy agency. Perceptions of child proxy agency are associated with obesity-related home environmental characteristics.
Keywords: Home; Proxy agency; Physical activity; Fruits and vegetables